Easy to say, hard to do. To the anniversary of two fundamental discoveries. Part 1 - A. Yu. Anisimov (Трансплантология (Москва), 2022)
On the eve of the anniversaries of two historical events: the 145th anniversary of the experiments in which Eck's fistula was performed and the 55th anniversary of the successful clinical approbation of the selective distal splenorenal anastomosis, a retrospective analysis of the key historical stages in the development of portal hypertension surgery from the first attempts to describe the anatomy of the hepatic vascular system, explaining its purpose in the body, the development of direct portocaval anastomosis, the widespread use of selective splenorenal anastomoses, to the Transjugular Intrahepatic Portosystemic Shunt procedure and orthotopic liver transplantation. At the same time, the emphasis is focused on the most colorful characters of researchers and clinicians who passed this path. The expediency of an integrated approach in solving the problems of portal hypertension with the development of both fundamental and applied clinical and organizational aspects is substantiated. It is shown that the discoveries born from the generalization of the results achieved by numerous researchers have contributed to a better understanding of this field of medicine, have become a solid foundation for what we have today and are a reliable platform for a successful start into the future.